Conversations about alcohol in healthcare - cross-sectional surveys in the Netherlands and Sweden - Latifa Abidi; Per Nilsen; Nadine Karlsson; Janna Skagerström; Amy O'Donnell (BMC, 2020)
Abstract Background This study evaluated and compared the extent, duration, contents, experiences and effects of alcohol conversations in healthcare in the Netherlands and Sweden in 2017. Methods Survey data in the Netherlands and Sweden were collected through an online web panel. Subjects were 2996 participants (response rate: 50.8%) in Sweden and 2173 (response rate: 82.2%) in the Netherlands. Data was collected on socio-demographics, alcohol consumption, healthcare visits in the past 12 months, number of alcohol conversations, and characteristics of alcohol conversations (duration, contents, experience, effects). Results Results showed that Swedish respondents were more likely to have had alcohol conversations (OR = 1.99; 95%CI = 1.64-2.41; p = < 0.001) compared to Dutch respondents. In Sweden, alcohol conversations were more often perceived as routine (p = < 0.001), were longer (p = < 0.001), and more often contained verbal information about alcohol's health effects (p = 0.007) or written information (p = 0.001) than in the Netherlands. In Sweden, 40+ year-olds were less likely to report a positive effect compared to the youngest respondents. In the Netherlands, men, sick-listed respondents, and risky drinkers, and in Sweden those that reported "other" occupational status such as parental leave, were more likely to have had alcohol conversations. Conclusions The results suggest that alcohol conversations are more common in healthcare practice in Sweden than in the Netherlands. However, positive effects of alcohol conversations were less likely to be reported among older respondents in Sweden. Our results indicate that alcohol preventative work should be improved in both countries, with more focus on risky drinkers and the content of the conversations in Sweden, and expanding alcohol screening in the Netherlands.